Unfolding the Chemistry of Learning at Home: A Phenomenological Study of Students Experiences with Home-Based Laboratory Worksheets - Obispo*, Kristoffer Paul Catungal; Ligsanan, Lucky Sonny (Universitas Syiah Kuala, 2025)
This phenomenological study explores the lived experiences of students using home-based laboratory worksheet in general chemistry during distance learning. As laboratory work is essential in science education, the shift to remote modalities required adaptive instructional strategies. Data were gathered through focus group discussions and teacher interviews, and thematically analyzed to capture students perceptions, challenges, and learning outcomes. Findings reveal that students experience active learning through discovery and hands-on engagement, facilitated by structured worksheet that supported independent experimentation. Many describe improved conceptual understanding as they explored real-life chemical reactions using everyday household materials. Despite positive learning experiences, participant also navigated challenges, including limited access to materials, unclear procedural guidance, trial-and-error approaches, and reliance on peer support. However, students displayed perseveranceand adaptability, highlighting the importance of well-designed instructional materials in remote learning context. Both students and teacher affirmed that the worksheet were effective in reinforcing prior knowledge and introducing new concept, contributing to satisfaction and meaningful learning. The study concludes that home-based laboratory worksheets were viable and engaging alternatives to traditional laboratory experiments, especially in times of limited access to physical laboratory and equipments. This model promotes self-directed learning, and deeper understanding of scientific concept, aligning with the goal of inclusive and quality science education